Pedagogical component of industrial pedagogical practice of students of higher education institutions: content and evaluation criteria - Zakharova, Svetlana N.; Mozhar, Alena N.; Redko, Mikhail P. (University Pedagogical Journal, 2024)
The article examines the main problems of organizing industrial pedagogical practice for students receiving a pedagogical specialty at the stage of basic higher education, provides a description of the pedagogical component of industrial practice, its goals and objectives at the present stage, content and evaluation criteria.
Keywords: higher education; training of teaching staff; pedagogical practice; evaluation criteria